(3GdeYdheGJ h eVGYaI GdKQhI GdGbJUGOjI h GdGfSGfjIs - (3MSfj YHO GdQMef(B, (3GdTjejs ((3GdbGgQI(B:s (3OGQ GdaLQ ddfTQ hGdJhRjY(B,s, 2009)
(3jVe NOeGJ GdecJHGJ hGdeYdheGJ heVGYaI GdbjeI, GdeYdheGJ hOhQgG aj UfGYI GdbQGQ, fehPL JWHjbj aj GdeVGYaI, GdbaRjI, GdJYde aj GdHjFI GdQbejI, GdJbfjGJ hGSJKeGQ GdhbJ, JfhY CfeGW GdYed aj GdHjFI GdQbejIs
Keywords: (3GdEbJUGO(B- (3NOeGJ GdeYdheGJs; (3GdeYdheGJs; (3eQGcR GdeYdheGJs